Pulse Dye Laser Therapy Successful for Elastosis Perforans Serpiginosa - Giulia Rinaldi; Alisha Chacko; Samira Batul Syed (Case Reports in Dermatological Medicine)
Background. We describe a case of elastosis perforans serpiginosa and its successful management with PDL laser. Case Presentation. A 15-year-old male presented with a history of itchy, raised, red and unsightly lesions on the back of his neck. He was diagnosed with Elastosis Perforans Serpiginosa on tissue biopsy and underwent pulse dye laser therapy over four years with excellent results. Conclusions. Our results show that pulse dye laser therapy is a safe and effective treatment for elastosis perforans serpiginosa.